2007
DOI: 10.1603/0022-0493(2007)100[551:eoaraa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Azinphos-Methyl Resistance and Activity of Detoxifying Enzymes in Codling Moth (Lepidoptera: Tortricidae) from Central Chile

Abstract: Regular applications of insecticides have been the main management practice against codling moth, Cydia pomonella (L.) (Lepidoptera: Tortricidae) in Chile. Organophosphates are the most widely used insecticides, and azinphos-methyl is an important element in spray programs. In particular, we evaluated diagnostic doses of azinphos-methyl on neonate and postdiapausing larvae from seven apple (Malus spp.) orchards. We also evaluated the activity of detoxifying enzymes, such as glutathione S-transferases (GSTs), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 23 publications
4
55
0
3
Order By: Relevance
“…Los resultados del presente estudio indican que existe alto flujo génico y ausencia de estructura poblacional entre huertos de manzano de las Regiones de O´Higgins y Maule, en una situación más parecida a la de Francia que a la de Sudáfrica. Estos antecedentes concuerdan con estudios realizados que muestran niveles incipientes de resistencia a insecticidas en C. pomonella provenientes de huertos con y sin aplicación de estos productos en las Regiones de O'Higgins y Maule (Reyes et al 2004;Fuentes-Contreras et al, 2007), los que sugieren una alta tasa de migración entre huertos independientemente de su tipo de manejo agronómico.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los resultados del presente estudio indican que existe alto flujo génico y ausencia de estructura poblacional entre huertos de manzano de las Regiones de O´Higgins y Maule, en una situación más parecida a la de Francia que a la de Sudáfrica. Estos antecedentes concuerdan con estudios realizados que muestran niveles incipientes de resistencia a insecticidas en C. pomonella provenientes de huertos con y sin aplicación de estos productos en las Regiones de O'Higgins y Maule (Reyes et al 2004;Fuentes-Contreras et al, 2007), los que sugieren una alta tasa de migración entre huertos independientemente de su tipo de manejo agronómico.…”
Section: Discussionunclassified
“…Por el contrario, Timm et al (2006) compararon poblaciones de C. pomonella de Sudáfrica mediante Polimorfismo de Longitud de Fragmentos Amplificados (AFLPs), encontrando diferenciación significativa entre poblaciones de diferentes localidades geográficas independientemente de la planta hospedera. Para el caso de Chile no existen antecedentes sobre la estructura y dinámica de las poblaciones de C. pomonella desde un punto de vista genético, aunque existen datos sobre resistencia incipiente a algunos insecticidas que sugieren que pueden existir altos niveles de flujo génico entre huertos con y sin aplicación de estos agroquímicos (Reyes et al, 2004;Fuentes-Contreras et al, 2007). Por lo tanto, el objetivo del presente estudio fue determinar la variabilidad genética y frecuencias genotípicas de poblaciones de C. pomonella provenientes de seis huertos de manzano de Chile Central, mediante la utilización de marcadores moleculares de tipo microsatélite desarrollados recientemente para esta plaga (Franck et al, 2005;Zhou et al, 2005).…”
Section: Introductionunclassified
“…Previous studies had found an increase in codling moth development time and a subsequent phenological delay of insecticide resistant individuals, which has been suggested as a pleiotropic cost of insecticide resistance (Boivin et al, 2005). Detectable levels of insecticide resistance have been reported in codling moth from both Washington (Varela et al, 1993;Knight, 2010d) and Maule (Reyes et al, 2004;Fuentes-Contreras et al, 2007), which may support the similar phenological differences found in Washington and Chile compared with Michigan in the 1970's. However, the similar experimental designs and several relevant differences with the methods used by Riedl et al (1976) may also account for these different models.…”
Section: Discussionmentioning
confidence: 65%
“…Larger body size is related to higher detoxification capacity, which confers resistance towards insecticides (Reyes et al, 2004(Reyes et al, , 2015Fuentes-Contreras et al, 2007). Therefore, females with larger body size have higher levels of insecticide resistance than do males with a smaller body size (Varela et al, 1993;Sauphanor et al, 2000;Reyes et al, 2004Reyes et al, , 2015Fuentes-Contreras et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in codling moth have found an association between insecticide resistance, body size, and sexual dimorphism because females have higher levels of resistance compared with males, which usually are of smaller body size (Varela et al, 1993;Sauphanor et al, 2000;Reyes et al, 2004Reyes et al, , 2015Fuentes-Contreras et al, 2007). Body size has also been related to dispersal capability in the codling moth: in the same population, larger females tend to be more fecund, live longer, and disperse less than smaller females (Gu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%